Iodine Status after a 3-Year Universal Salt Iodisation in Sarawak, Malaysia - Lim, Kuang Kuay; Jambai Endu,; Chan, Ying Ying; Teh, Chien Huey; Hasimah Ismail,; Lim, Kuang Hock; Kee, Chee Cheong (Universiti Kebangsaan Malaysia, 2015)
Introduction Following the reveal of borderline iodine sufficiency among the Sarawakians from the 2008 National Iodine Deficiency Disorders (IDDs) survey, a mandatory universal salt iodization (USI) was implemented in Sarawak thereafter. This study aimed to determine the current status of USI in Sarawak after a 3-year implementation of USI from 2008 to 2011. Methods The IDD survey was conducted between Jun 2011 to July 2011 involving six districts in Sarawak (Sarikei, Mukah, Kapit, Sibu, Bintulu and Miri). The schools were selected via multistage proportionate-to-population size sampling technique and the children were randomly selected via systematic sampling. A total of 19 schools and 661 children were recruited into the survey. Thyroid size was determined by palpation and was and graded according to the classification of the World Health Organization (grade 0-2). The iodine excretion level in spot morning urine was measured using inhouse microplate method. The urinary iodine concentration (UIC) values were compared by Kruskal-Wallis test and Chi-square tests were used to compare categorical variables. Results total of 610 school children were participated in the study (92.3%). The TGR of grade 1 and 2 was found to be 0.3% (n = 2). Overall the median UIC level was 154.2 (IQR, 92.7 - 229.8) μg/L, with the highest median UIC been observed in Sarikei [178.0 (IQR, 117.6 - 308.9) μg/L], followed by Mukah [174.8 (IQR, 99.0 - 224.3) μg/L)], Miri [158.6 (IQR, 92.3 - 235.4) μg/L], Sibu [147.0 (IQR, 89.8 - 221.4) μg/L], Bintulu [142.3 (IQR, 52.8 - 245.1) μg/L] and Kapit [131.0 (IQR, 88.6 - 201.9) μg/L]. One in every ten child was of iodine deficient (UIC < 50μg/L) while a third of the child (32%) were of adequate level of UIC. Conclusion The present findings indicate that the mandatory USI successfully improves the iodine level of children in Sarawak. However, regular and proper monitoring of the UIC level in the communities is needed to prevent excessive iodine intake.